The Penetanguishene Decision: To Be a Naval Yard or Not to Be - Malcomson, Thomas (Ontario History, 2021)
His Majesty’s Naval Establishment for Lake Huron has been portrayed as deriving from a decisive decision, in the wake of the War of 1812, that resulted in a significant, active naval yard being developed on the shores of Penetanguishene Bay. This picture ignores the earlier plans for its development, and the protracted period of indecision that marked its beginning. Once built, the potentially significant establishment was rendered impotent through a continuous series of reductions that left a handful of men in charge of five decaying vessels in ordinary.